Archaea S‐layer nanotube from a "black smoker" in complex with cyclo‐octasulfur (S8) rings. Issue 12 (11th October 2017) - McDougall, Matthew; Francisco, Olga; Harder‐Viddal, Candice; Roshko, Roy; Meier, Markus; Stetefeld, Jörg
Abstract: Elemental sulfur exists primarily as an S 8 0 ring and serves as terminal electron acceptor for a variety of sulfur‐fermenting bacteria. Hyperthermophilic archaea from black smoker vents are an exciting research tool to advance our knowledge of sulfur respiration under extreme conditions. Here, we use a hybrid method approach to demonstrate that the proteinaceous cavities of the S‐layer nanotube of the hyperthermophilic archaeon Staphylothermus marinus act as a storage reservoir for cyclo‐octasulfur S 8 . Fully atomistic molecular dynamics (MD) simulations were performed and the method of multiconfigurational thermodynamic integration was employed to compute the absolute free energy for transferring a ring of elemental sulfur S 8 from an aqueous bath into the largest hydrophobic cavity of a fragment of archaeal tetrabrachion. Comparisons with earlier MD studies of the free energy of hydration as a function of water occupancy in the same cavity of archaeal tetrabrachion show that the sulfur ring is energetically favored over water.